Blood group type A secretors are associated with a higher risk of COVID‐19 cardiovascular disease complications. Issue 2 (2nd April 2021) - Mankelow, Tosti J.; Singleton, Belinda K.; Moura, Pedro L.; Stevens‐Hernandez, Christian J.; Cogan, Nicola M.; Gyorffy, Gyongyver; Kupzig, Sabine; Nichols, Luned; Asby, Claire; Pooley, Jennifer; Ruffino, Gabriella; Hosseini, Faroakh; et al.
Abstract: The SARS‐CoV‐2 virus causes COVID‐19, an infection capable of causing severe disease and death but which can also be asymptomatic or oligosymptomatic. We investigated whether ABO blood group or secretor status was associated with COVID‐19 severity. We investigated secretor status because expression of ABO glycans on secreted proteins and non‐erythroid cells are controlled by a fucosyltransferase (FUT2), and inactivating FUT2 mutations result in a non‐secretor phenotype which protects against some viral infections. Data combined from healthcare records and our own laboratory tests ( n  = 275) of hospitalized SARS‐CoV‐2 polymerase chain reaction positive patients confirmed higher than expected numbers of blood group A individuals compared to O (RR = 1.24, CI 95% [1.05, 1.47], p  = 0.0111). There was also a significant association between group A and COVID‐19‐related cardiovascular complications (RR = 2.56, CI 95% [1.43, 4.55], p  = 0.0011) which is independent of gender. Molecular analysis revealed that group A non‐secretors are significantly less likely to be hospitalized than secretors. Testing of convalescent plasma donors, among whom the majority displayed COVID‐19 symptoms and only a small minority required hospitalization, group A non‐secretors were slightly over‐represented. Our findings showed that group A non‐secretors are not resistant to infection by SARS‐CoV‐2, but are more likely to experience a less severe form of associated disease.